Investigating Factors Affecting the Attraction and Retention of Overseas Teachers in the United Arab Emirates - Lalich, Damon Robert (Curtin University, 2021)
This mixed-method study investigated the attraction and retention of overseas teachers in the United Arab Emirates. The study, involving 866 participants, identifies the types of motivators that make international teacher relocation most viable along with the key obstacles to successful teacher adjustment. The study provides valuable contributions to the decision making of education administrators through identifying the attributes of teachers who are most likely to succeed in the host country.